Science in Society - Zehr, Stephen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course evaluates the positions of science in and as society. Science in society refers to the increasingly important role that science lays in social structural arrangements, social change, and social interaction. For example, science plays an important role in how we perceive the environment or in how we make decisions about guilt and innocence in courts of law. Science as society refers to social aspects of the production of scientific knowledge. That is, the construction of scientific knowledge can be analyzed as a social process and the products themselves as social entities. We will see how scientific knowledge and scientists are shaped by broader social, cultural, and political forces.